Bridging Theoretical Paradigms and Professional Praxis (Technological Enhancement in Maritime Engineering Education Through Industry-Academia Collaboration) - Marihot Simanjuntak; Brenhard M. Tampubolon; Junaidi Junaidi; Femmy Sofie Schouten; M.Ridwan; M. Mudakir (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Maritime engineering education confronts unprecedented technological disruption requiring fundamental reconceptualization of how professional expertise transforms into pedagogical innovation. This investigation penetrates the phenomenological intersection where operational maritime knowledge encounters structured academic environments, revealing sophisticated dynamics that transcend conventional technology transfer paradigms. Through qualitative exploration of eight strategically selected participants—maritime entrepreneurs with engineering foundations and academic practitioners specializing in maritime science—this research unveils remarkable convergence around technological enhancement imperatives. Stakeholders demonstrate 92% alignment regarding current educational limitations while identifying substantial improvement trajectories across critical competency domains. The investigation reveals dramatic enhancement potential: environmental awareness competencies advance 46%, problem-solving integration capabilities improve 39% through systematic technological integration approaches. Simultaneously, concerning misalignment emerges between industry technological demands and educational preparedness, with gaps reaching 37% in predictive maintenance and 35% in environmental compliance domains. This research establishes innovative frameworks for understanding professional-academic knowledge symbiosis while creating practical pathways for sustainable technological enhancement that honors both operational expertise and educational rigor within contemporary maritime engineering contexts.